Nilai Spiritual pada Hiasan Kuno Rumah Tjong A Fie: Studi Semiotika - Ishtifa, Alsaumi (Universitas Harapan Medan, 2024)
This study has the aim of finding ornaments and the meaning behind the symbols on the ornaments found in the Tjong A Fie Mansion building. In its meaning, the researcher uses the theory of Roland Barthes. This research is a qualitative research, with data collection techniques of observation or field research, documentation, direct and indirect interviews with museum managers and curators as well as staff of Tjong A Fie Mansion and also looking for other sources of information from the internet and some references from previous research. The researcher focuses on providing knowledge about one of the tourism icons of the city of Medan to readers by examining the ornaments that are closely related to the cultural and religious values with semiotic approach ​​adopted by Tjong A Fie as the owner of the building. there is a meaning behind the symbols in every ornament on the Tjong A Fie Mansion building, Bat (Fu), Phoenix (Hong Bird), Dragon (Lung), Qilin, Plum Blossom, Peony Blossom, Bamboo Tree, Fu Lu Shou Symbol, Three-legged Frog, and the last Lantern.